“FIZIKANÍ OQÍTÍW METODIKASÍ” PÁNINEN ÁMELIY ShÍNÍǴÍWLARDÍ ÓTKERIW METODIKASÍ - Karlıbaeva, G.E. (ILIM hám JÁMIYET, 2025)
This article discusses the introduction of such an important pedagogical principle as “effective modern interactive teaching technologies in the educational process” in order to improve the quality of physics teaching methods in our country. At the same time, we strive to effectively use the methods “Cluster”, “Essay”, “BYOD”, “Gallery”. Using these they have the ability to think freely, think creatively and intellectually, express their thoughts clearly, defend the opinions of others and express critical views.